Intraguild predation by Tupiocoris cucurbitaceus on Encarsia formosa and its influence on biological control of Trialeurodes vaporariorum - Cuello, Eliana Marina; Lopez, Silvia Noemi (Department of Agroenvironmental Sciences and Technologies, Università di Bologna, 2024)
The predator Tupiocoris cucurbitaceus (Spinola) and the parasitoid Encarsia formosa Gahan are natural enemies of Trialeurodes vaporariorum (Westwood) that can be found simultaneously in greenhouse tomato crops. Whether or not these species are involved in a trophic interaction with each other, and how this interaction might impact the control of the whitefly population has not been explored so far. In the present study, we evaluate the consumption and preference of T. cucurbitaceus for parasitized and nonparasitized T. vaporariorum nymphs. Furthermore, the effect that the joint presence of both natural enemies can have on the control of the whitefly population. Our results show that under laboratory conditions T. cucurbitaceus females engage in intraguild predation on E. formosa pupae. However, given the choice, the predator prefers to prey on healthy T. vaporariorum nymphs. Under greenhouse conditions, however, both T. cucurbitaceus and E. formosa reduce whitefly population when released separately, and their control is enhanced when released together.